Development of antifungal edible coating for strawberry using fruit waste. Issue 11 (26th September 2021) - Saeed, Muhammad; Azam, Muhammad; Saeed, Farhan; Arshad, Umair; Afzaal, Muhammad; Bader Ul Ain, Huma; Ashraf, Jahanzaib; Nasir, Zamara
Abstract: The study was designed to prepare an edible antifungal coating of orange peel essential oil and carnauba wax against Penicillium expansum in strawberry. Orange peel essential oil was extracted using water distillation and was used to develop coating with carnauba wax. Prepared coating was applied to strawberries using different concentrations of orange peel oil (To, T1, T2, T3, T4, and T5 for 0, 1, 2, 3, 4, and 5%). The physicochemical, microbial, and sensory analyses were performed during storage. The weight of the strawberries decreased during storage. The firmness and microbial load were increased during storage. An increasing trend was observed for TSS, weight loss, and anthocyanin content. Minimum inhibitory concentration of orange peel oil was 0.35 μL/mL with 96% maximum growth inhibition against P. expansum . The coating materials did not exert negative effect on sensory characteristics. The sensory and keeping qualities were better as compare to the control. Comparatively, better results were observed for coated strawberries with T3 (3%) as best treatment. Practical application: Postharvest losses resulted in 40%–50% wastage in globally produced fruits and vegetables. Edible coating is one of the methods that help to reduce spoilage of fresh fruits and vegetables. In this study, orange peel essential peel and carnauba wax have shown the potential to reduce fresh food losses in strawberry. OPEO coating extended the storage life of strawberry, while maintaining quality attributes of the fruits. Using the finding of this study, application of OPEO and carnauba wax edible coating to strawberry stored at ambient conditions can prevent mold growth on strawberry. This edible coating containing natural bioactive compounds can be used as an alternative to synthetic preservatives and can help to avoid cold storage expenses.